Atlas Linguístico dos Sertões Cearenses (ALSCE) - Lima, Fabiana dos Santos (2019)
The Linguistic Atlas of the Sertões Cearenses (ALSCE) is a PhD conclusion work that aims to document the Cearense speaking, specifically from the Sertões Cearenses mesoregion, through the geolinguistic method whose main characteristic is to collect data and represent them by means of letters linguistic. This study was developed based on the multidimensional Geolinguistics methodology that is present in the Atlas Linguistic Project of Brazil (ALIB, 2013). Therefore, ALSCE proposed to carry out a more systematic survey of the lexicon and morphosyntax of this mesoregion to continue the geolinguistic studies initiated by the already existing atlas in Ceará. As the chosen region is a great socio, economic, political, and cultural center of the State of Ceará, it contains a great linguistic framework to be researched. To support this work, theorists were discussed who discuss the important role of dialectology and geolinguistics for the study of a linguistic inventory. Among them, the following stand out: ARAGÃO (1983, 2007), CÂMARA JR (2004), CARDOSO E FERREIRA (1994), COSERIU (1987), LABOV (2008), MONTEIRO (1995), ROMANO (2015) AND THUN ( 1999). The research was carried out following the principles of modern Geolinguistics, recording diatopic and diastratic parameters of the chosen geographical space, by controlling 3 variables: sex, age and education. Thus, a linguistic network was constructed with 9 survey points, where 8 people were interviewed in each one, making a total of 72 informants. Of these, 36 are men and 36 women, according to the criterion of the gender variable; with ages between 18 and 30 years and 45 and 60 years, and education in two modalities: informants with education level up to High School (HS) and informants with University Education (UE). The questionnaires for obtaining the collected data were the Lexical Semantic Questionnaire (QSL) and the Morphosyntactic Questionnaire (QMF) of the ALiB Project and the operational tool for generating the letters was the software for making linguistic letters called [SVGCLIN]. With that, 80 semantic-lexical letters were produced, covering all lexical items covered by the atlases produced in the State until then, and 30 morphosyntactic letters, addressing the most pertinent aspects to the morphosyntax of Ceará speaking, making a total of 110 linguistic letters. Thus, one can find lexical letters such as Letter L01- Riacho, Letter L31 - Vereda, Letter L50 - Sovaqueira and Letter L77 - Sweet tooth, and morphosyntactic letters like Letter M09 - Plural of Bread, Letter M16 - Pronouns We / a people and Letter M24 - By (1st PS). Therefore, when registering the spoken language of the Sertões Cearenses, it is possible to perceive the socio-cultural influences on the language in their daily lives, strengthening their 12 linguistic roots. Thus, despite all the complexity of geolinguistic research, the production of a linguistic atlas can still provide good research and reduce the distance between the academy and the classroom.